Pelatihan Akuntansi UMKM Berbasis Excel kepada Musyawarah Guru Mata Pelajaran Ekonomi, Provinsi Daerah Istimewa Yogyakarta - Pratama, Yohanes Mario; Widyatini, Ignatia Ryana; Budiharta, Pratiwi; Ardiati, Aloysia Yanti; Purwaningsih, Anna; Budisantoso, A. Totok; Iswari, Tabita Indah; Kurniawati, Anggreni Dian (Jurnal Atma Inovasia, 2023)
MGMP Economics is a forum for high school teachers in economics subjects which was formed in order to discuss and solve problems related to the economics learning process. Every educator is encouraged to improve professional skills in their respective fields, one of which is financial literacy. This Community Service aims to provide Excel-based EMKM accounting training with the aim of providing knowledge regarding the importance of accounting in a business, especially MSMEs. This service method is in the form of face-to-face counseling on August 3, 2023. The participants are given training regarding basic accounting equations, profit and loss reports, statements of financial position, and the accounting cycle using Excel. Simple exercises are the material for discussion in this training so that participants can understand them well. The participants took part in this training enthusiastically and were able to understand material related to the preparation of EMKM financial reports using Excel. Keywords — MSME, MGMP Economics, MSME’s Accounting, Financial Report, Excel MGMP Ekonomi adalah wadah guru SMA mata pelajaran ekonomi yang dibentuk dalam rangka membahas dan menyelesaikan permasalahan terkait proses pembelajaran ekonomi. Setiap pendidik didorong untuk meningkatkan kemampuan profesional di bidangnya masing-masing, salah satunya literasi keuangan. Pengabdian Masyarakat ini bertujuan untuk memberikan pelatihan akuntansi EMKM berbasis excel dengan tujuan untuk memberikan pengetahuan terkait pentingnya akuntansi dalam suatu usaha, khususnya UMKM. Metode pengabdian ini berupa penyuluhan secara tatap muka pada tanggal 3 Agustus 2023. Para peserta diberikan pelatihan terkait persamaan dasar akuntansi, laporan laba rugi, laporan posisi keuangan, dan siklus akuntansi menggunakan excel. Latihan-latihan soal sederhana menjadi bahan diskusi dalam pelatihan ini supaya peserta dapat memahami dengan baik. Para peserta mengikuti pelatihan ini dengan antusias dan dapat memahami materi terkait penyusunan laporan keuangan EMKM menggunakan excel. Kata Kunci—UMKM, MGMP Ekonomi, Akuntansi EMKM, laporan keuangan, Excel